Problems and Constraints of Agricultural Labourers in Gudiyattam Block of Vellore District in Tamil Nadu - YOGANANDHAM, Dr. G. (The journal of contemporary issues in business and government, 2021)
The economy of Tamil Nadu is agro-forestry based economy based on agriculture and its associated activities. Among the blocks in Tamil Nadu Gudiyattam Block of Vellore district is agriculturally developed one. Agricultural labourers constitute overwhelming majority segment of operational inhabitants. Their number in Tamil Nadu as per 2011 census is around 3.25 millions. In agricultural harvesting process both male and female labourers are employed. In all purpose merely male workers were working because they are the emotionally involved workers when compare to their counterpart. They live in poorly built-up and socially low status houses, starving and malnourished. Their educational, economic and social statuses are also very low when we compare to the main stream of the society. Without providing proper importance given to agricultural labourers concerning the living environment is enhanced, no country can attain real progress and development in agriculture. In this background, this study concentrates on the problems and constraints of agricultural labourers in Gudiyattam Block of Vellore District in Tamil Nadu.